2011
DOI: 10.17221/7/2011-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of transgenic cotton (Gossypium hirsutum L.) plants by loop-mediated isothermal amplification

Abstract: Abstract:In an attempt to speed up the process of screening of transgenic cotton (G. hirsutum L.) plants, a visual and rapid loop-mediated isothermal amplification (LAMP) assay was adopted. Genomic DNA was extracted from fresh leaf tissues of T 2 transgenic cotton containing chitinase (chi) and cry1A(b) genes. Detection of genes of interest was performed by polymerase chain reaction (PCR), LAMP and real-time PCR methods. In LAMP assay the amplification was performed after 30 min at 65°C when loop primers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It revealed that loop primers reduced the reaction time to 20 min only (Rostamkhani et al . ; Mashooq et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It revealed that loop primers reduced the reaction time to 20 min only (Rostamkhani et al . ; Mashooq et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…whereas it takes 45 min without loop primers for microbial detection. It revealed that loop primers reduced the reaction time to 20 min only (Rostamkhani et al 2011;Mashooq et al 2016). The positive samples were visualized by turbidity and colour detection with the addition of DNA-intercalating dyes like SYBR green I dye.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification of the gene of interest was carried in the presence of loop primers that greatly reduced the time, otherwise, utilized by conventional PCR process. A rapid DNA extraction followed by LAMP assay is claimed to take about 30 min (Rostamkhani et al 2011) and the obtained products can be visually observed in reaction tube upon observing the turbidity. Surface plasmon resonance (SPR) is another biomolecule based detection system that can easily identify transgenic cotton within 5 min per sample.…”
Section: Methods For Confirmation Of Transformationmentioning
confidence: 99%
“…This can be potentially used for tests in the field (Punati et al, 2019;Joon et al, 2019;Tumino et al, 2020). In addition, LAMP has been extensively applied in food-borne pathogens, allergens, and genetically modified organisms in food analysis (Hara-Kudo et al, 2010;Rostamkhani et al, 2011;Saharan et al, 2015;Shi et al, 2017;Yuan et al, 2018;Li et al, 2019;Zhuo et al, 2019;Tumino et al, 2020). Furthermore, LAMP products traditionally observed by gel electrophoresis and hydroxynaphthol blue (HNB) or SYBR are either difficult to distinguish by fluorescent dyes, which need special equipment and the process is time-consuming, or easily exposed to aerosol pollution due to the opening of the lid (Shi et al, 2017;Punati et al, 2019;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%